Genetic dating and pattern of admixture in modern human evolution - Defo, Joel (Institute of Infectious Disease and Molecular Medicine, 2017)
Genetic variation is shaped by admixture between populations in an evolutionary process. The mixture dynamic between groups of populations results in a mosaic of chromosomal segments inherited from multiple ancestral populations. The distribution of ancestral chromosomal segments and the recombination breakpoints in an admixed genome provide information about the time of admixture. Studying populations with particular ancestries has become a major interest in population genetics because of medical and evolutionary impacts of the patterns of single nucleotide polymorphisms. It provides a better understanding of the impact of population migrations and helps us uncover interactions between several populations. Most of the research on admixed population dating has focused on a single interaction between two populations using various approaches. Some have extended this to mixing of three populations based on assumptions and approaches which differ from one tool to another. However, the inference of distinct ancestral proportions along the genome of an admixed individual and plausible dates of admixture, still remain a challenge in the case of multi-way admixed populations. This dissertation consists of three research initiatives. First, provide a succinct review of current methods for dating the admixture events. We accomplish this by providing a comprehensive review and comparison of current methods pertinent to date admixture event. Second, we assess various admixture dating tools which estimate the time of admixture between two parental populations. We do so by performing various simulations assuming a particular number of generations and use these to evaluate the tools. Third, we apply the top three assessed methods to some admixed populations from the 1000 Genomes project. Despite MALDER shows improvement and produces reasonable date estimates over other current methods, the results from both simulation and real data suggest that dating ancient admixture events accounting for the effect of other admixtures remains a challenge. Our results suggest the need for developing a new approach to date ancient and complex admixture events in multi-way admixed populations.